Modifications and Pharmaceutical Applications of Glucomannan as Novel Pharmaceutical Excipient in Indonesia: Review Article - Nuur Aanisah; Yoga Windhu Wardhana; Anis Yohana Chaerunisa (Universitas Sebelas Maret, 2022)
Currently, Indonesia is excessively dependent on imported raw materials, such as pharmaceutical excipients. In this regard, the current pandemic should remind the critical nature of independence in purchasing raw resources to cope with future dynamics. One of the causes of dependence is the lack of raw materials management, specifically from biological sources abundantly available. A significant advantage is directed towards natural excipients because large quantities of more affordable plants ensure sustained availability in nature. Therefore, this study highlighted the possibility of using excipients derived from natural resources that are commonly used yet underutilized in Indonesia, such as glucomannan (GM). Indonesia has the potential to produce GM, considering the high natural resources as its source. However, it has not been applied extensively in pharmaceutical preparations due to diverse uses in several countries' drug, food, and cosmetic industries. This study aimed to discuss the modifications of GM and their use as pharmaceutical excipients with better physical properties. Additionally, the potential of melinjo seeds that have not been widely used was also analyzed. Melinjo seeds can be used as a source of GM due to their fairly large polysaccharide of about 64.11%. This issue will promote national autonomy in developing novel pharmaceutical excipients derived from natural resources that are highly economical and innovative.